Analisis Penerapan Tax Planning PPH 21 Sebagai Upaya Meningkatkan Efisiensi Pajak Penghasilan Badan - Hendrawan Hendrawan; Putri Awalina; Agus Athori (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Taxes have a central role in state revenue to finance government spending and development. Public awareness as taxpayers is an important aspect in securing state revenue. Tax planning as a strategy to optimize company tax obligations. Implementation of tax planning (Tax Planning) can use several methods such as the Gross Up Method, Gross Method, and Nett Method.This research was conducted at the Bangun Jaya Bersama Cooperative in Blitar City, East Java. Because this company has not implemented special procedures for PPh article 21, and the research aims to analyze how implementing tax planning strategies can increase the efficiency of corporate income tax in cooperatives. The results of tax planning research to increase corporate income tax tax efficiency show that the Nett Method is better than the Gross Method and Gross up Method. This is based on data obtained by the Nett Method which is more profitable for the company, the efficiency obtained is 1.48%.